Development and Validation of an UV-Derivative Spectrophotometric Method for Determination of Glimepiride in Tablets - Bonfilio, Rudy [UNESP]; de Araujo, Magali B.; Salgado, Hérida Regina Nunes [UNESP] (Soc Brasileira Quimica, 2011)
Glimepiride is an oral antidiabetic drug widely used in treatment of type 2 diabetes. This work proposed the development and validation of a derivative UV spectrophotometric method for determination of glimepiride in tablets. The quantification of glimepiride in 5x10(-3) mol L(-1) NaOH was performed by using a wavelength interval of 8 nm in the range of 220-300 nm. The amplitude values obtained in the second-derivative spectra were arbitrary units of the peak height from the central zero base line to the signals obtained at 279.0, 257.5 and 256.3 nm for quantification of Amaryl (R) tablets 1 mg, Amaryl (R) tablets 2 mg and Amaryl (R) tablets 4 mg, respectively. The method was completely validated according to the International Conference on Harmonization (ICH) guidelines, showing accuracy, precision, selectivity, robustness and linearity. The validated method is suitable for quality control applications, since it does not use polluting reagents, it is simple and has low-cost.
Keywords: glimepiride; validation of pharmaceutical methods; derivative-UV spectrophotometry; pharmaceutical quality control